The promise of the science commons and the tragedy of intellectual property rights: The university's IPR policy in perspective - Niceto S. Poblador (University of the Philippines, School of Economics (UPSE), 2012)
The title of this essay is a play of words on The Tragedy of the Commons, the title of the landmark paper by Garrett Hardin which appeared in Science in 1968. After a long period of dormancy, the concept was resuscitated by Elinor Ostrom in 1990 in a book which gained her the Nobel Prize in Economics in 2011. Science Commons is one of an increasing number of academic and scientific advocacy groups that seek to promote open access to published works and data for the purpose of capturing the enormous potential value from the vast numbers of researches being turned out by individuals, businesses, universities and research institutions all over the world (http://sciencecommons.org/projects/publishing/). By commons, Hardin and Ostrom meant communally owned and used resources such as grazing lands, forest resources, mineral resources and so on the unmitigated use of which lead to their eventual exhaustion or destruction. By contrast, the 'commons' in science commons refers to knowledge and information, resources that follow a totally different economic logic from those that apply to physical resources. Property rights and other governance mechanisms that apply to one do not necessarily apply to the other.
Keywords: 330; Immaterialgüterrechte; Universitäre Forschung; Wissenstransfer